2021
DOI: 10.1177/23259671211030883
|View full text |Cite
|
Sign up to set email alerts
|

Patterns and Distribution of Deep Vein Thrombosis and Its Effects on Clinical Outcomes After Opening-Wedge High Tibial Osteotomy

Abstract: Background: Although a few studies have reported the incidence of deep vein thrombosis (DVT) after opening-wedge high tibial osteotomy (OWHTO), previous studies focused only on symptomatic DVT. Information is lacking regarding the overall incidence of DVT after OWHTO, thrombus location, and the relationship between DVT and clinical outcome. Purpose: To determine the overall incidence of DVT and classify the location of DVT after OWHTO. We also determined whether significant differences in clinical improvement … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 40 publications
(62 reference statements)
1
6
0
Order By: Relevance
“…The proportion of patients with muscular DVT was 95.2% (20/21), and that of axial DVT was 76.2% (16/21). In the present study, the results were comparable to those of Park et al 29 . The incidence of DVT was 38.9% (7/18) and 57.1%(8/14)in control group and 0.5 g TXA group, respectively.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…The proportion of patients with muscular DVT was 95.2% (20/21), and that of axial DVT was 76.2% (16/21). In the present study, the results were comparable to those of Park et al 29 . The incidence of DVT was 38.9% (7/18) and 57.1%(8/14)in control group and 0.5 g TXA group, respectively.…”
Section: Discussionsupporting
confidence: 91%
“…Complications after MOWHTO usually include: delayed wound healing, wound infection, hematoma, loss of correction, intraoperative or postoperative lateral cortex fractures, DVT, bone delayed unions, vascular injury and so on 25–27 . The incidence of DVT of lower extremities had been reported to range from 1% to 44.7% 19,26,28,29 . Park et al 29 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A retrospective study by Onishi et al reported the incidence of DVT after osteotomies around the knee (13.8%) [28], but the study was not specific to OWHTO. Later, Park et al further reported the incidence (44.7%) and location (76.2% around the osteotomy site) of immediate postoperative DVT based on the clinical data from 46 patients with OWHTO [30], but did not analyze associated risk factors. A prospective Japanese study with 137 subjects revealed that the postoperative single‐leg standing test was the independent predictor of immediate postoperative DVT after OWHTO [19].…”
Section: Introductionmentioning
confidence: 99%
“…Immediately postoperative deep vein thrombosis (DVT) is a highly prevalent medical complication (2.4–44.7%) following open wedge high osteotomy (OWHTO) [18, 23, 26, 30], despite prophylactic anticoagulation. DVT not only causes swelling of the affected limb, interfering with local circulation and compromising the healing of the surgical site and osteotomy gap but also may extend proximally, leading to pulmonary embolism (PE) and even death [12].…”
Section: Introductionmentioning
confidence: 99%